- ANALYSIS OF THE EFFECT OF THE AUKUS (AUSTRALIA, UNITED KINGDOM AND UNITED STATES OF AMERICA) DEFENSE PACT ON INDO-PACIFIC SECURITY: - - Batudoka, Mohammad Damayantar Etnik (Mediasi Journal of International Relations, 2023)
The AUKUS (Australia, United Kingdom, and the United States of America) Defense Pact, inaugurated on September 15, 2021, has affected countries in the Indo-Pacific Region. This study aims to analyze the effect of the AUKUS Defense Pact on security in the Indo-Pacific Region. The research method used in this study is a qualitative approach with descriptive analysis, in which data relevant to the object of research are collected through library research. The analysis is carried out using a realism approach with a focus on the concept of trilateral security alliances and security dilemmas. The study results show that the presence of the AUKUS Pact in the Indo-Pacific Region can affect regional security governance, including developing defense technology, military cooperation, and foreign policy. This Pact raises concern from countries in the area about AUKUS intentions in securing the Indo-Pacific Region, especially with the plan to build a nuclear submarine which has becom e controversial. On the other hand, several countries in the Indo-Pacific Region also face a security dilemma due to the AUKUS Defense Pact, especially China and several ASEAN countries, which feel threatened by the presence of AUKUS. AUKUS has led to China increasing its military activity in response to what it perceives as threats to its country's security. In addition, polemics among countries in the Indo-Pacific Region in response to AUKUS also shows the complexity of the security of the Indo-Pacific Region.